THE INFLUENCE OF SOCIAL SUPPORT ON THE SELF-ADJUSMENT OF DRUG OFFENDERS IN CLASS I CIPINANG CORRECTIONAL INSTITUTION - Divanda, Muhammad Hanif; Wibowo, Padmono (Journal of Management Small and Medium Enterprises (SMEs), 2025)
The purpose of this research was to determine the effect of social support on the adjustment of narcotics prisoners at the Cipinang Class I Correctional Institution. This research used quantitative methods with a non-probability sampling technique of 108 prisoners. The data collection technique was carried out using questionnaires distributed directly to prisoners. There are 22 statements used as indicators in this research. The data analysis technique used is through the normality test, simple linear regression test, significance test, and determination test which were processed using IBM SPSS version 25 software. The results of the research show there is an influence of social support on adjustment. The results of the determination test shows that the knowledge sharing behavior variable has an influence of 54.3% on the innovative work behavior variable, while the remaining 45.7% is influenced by other variables not explained in this research. From the results of this research, it can be concluded that there is a positive and significant influence between social support and adjustment at the Cipinang Class I Correctional Institution. Keywoards : Social Support; Adjustment; Class I Cipinang Correctional Institution